Preparation of a separable composite of Fe3O4@SiO2@MnO2 magnetic submicrospheres as an efficient adsorbent for the highly sensitive determination of tetracyclines in aquatic products - Junlu, Bai; Pengfei, He; Junjie, Zeng; Xiaojun, Zhang; Peipei, Li (Microchemical journal, 2025)
[Display omitted] •Fe3O4@SiO2@MnO2 composites can effectively improve the agglomeration of Fe3O4 magnetic cores and enhance the enrichment of target compounds.•Fe3O4@SiO2@MnO2 is successfully applied to remove tetracycline residues from aquatic products by MSPE.•By integrating MSPE with UHPLC-MS/MS, a sensitive and reproducible method for tetracycline detection in aquatic products was developed. In this research, a MnO2-coated composite magnetic nano-microsphere (Fe3O4@SiO2@MnO2) was synthesized and employed as an adsorbent for magnetic solid phase extraction (MSPE) in pretreatment of trace tetracyclines (TCs) in aquatic products. The characterization results showed that the Fe3O4@SiO2@MnO2 nanocomposite exhibited a larger specific surface area and a greater number of active sites. By combining the optimized MSPE conditions with ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS), an accurate and sensitive method for the determination of 4 TCs, including oxytetracycline (OTC), Tetracycline (TC), chlortetracycline (CTC) and doxycycline (DC) was developed. Experimental variables of MSPE including solution pH, adsorbent dosage, adsorption time, and eluent selection were investigated and optimized systematically. In addition, the developed method showed good linearity (R2 ≥ 0.999), low LODs (0.15–0.18 ng·g−1), and LOQs (0.51–0.61 ng·g−1). The recoveries of TCs were ranged from 89.21 % to 99.45 %, with relative standard deviations (RSD) less than 10.37 % in aquatic samples. Compared to the traditional extraction methods, using this nano-composites for TCs analysis in aquatic products is more sensitive, effective and convenient.